Ethanolic extract of mangosteen (Garcinia mangostana) pericarp as sensitivity enhancer of doxorubicin on MCF-7 cells by inhibiting P-glycoprotein: - - NI PUTU LINDA LAKSMIANI (Smujo International, 2019)
Abstract. Laksmiani NPL. 2019. Ethanolic extract of mangosteen (Garcinia mangostana) pericarp as sensitivity enhancer of doxorubicin on MCF-7 cells by inhibiting P-glycoprotein. Nusantara Bioscience 11: 49-55. Generally, doxorubicin is used in combination with other anticancer agents. Reduction side effects tend to be better in combination use than the use of single doxorubicin. Therefore the development of anticancer agents with low side effects and combination agents that decrease the side effects of doxorubicin still need to be pursued. The use of doxorubicin also shows a phenomenon of resistance due to over-expression of P-glycoprotein (Pgp). The research was conducted to evaluate the cytotoxic effect of lower dose doxorubicin combine with ethanolic extract of mangosteen pericarp (EEMP) on MCF-7 cells and determine the mechanism of alpha (a)-mangostin as the active compound in EEMP that contribute increasing sensitivity of doxorubicin on MCF-7 through Pgp by in silico. The cytotoxic activity was observed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Molecular docking with 4.2 autodock program was used to evaluate the interaction of a-mangostin with Pgp. EEMP has IC50 of 54 ?g/mL on MCF-7 cells while for doxorubicin has IC50 of 1392 nM. Exposure EEMP enhanced cytotoxic effect of doxorubicin on MCF-7 cells. Solely doxorubicin 750 nM treatment gave cell viability percentage 94.98%, but when combined with EEMP 22.5 ?g/mL, the cell viability percentage was reduced to 16.91%. This shows that EEMP potent to be used as a combination agent for doxorubicin chemotherapy. The in silico assay demonstrate that a-mangostin has an affinity for Pgp with binding energy of -6.13 kcal/mol. Keywords: EEMP, doxorubicin, MCF-7, Pgp, combination